Development of Coordinated Control of Vehicle Traffic Flow at Adjacent Intersection - Kurniawan, Freddy; Jusoh, Muzammil; Muminov, Bahodir; Alam, Hermansyah; Dermawan, Denny; Purnomo, Muhamad Jalu (Institut Teknologi Dirgantara Adisutjipto, 2025)
Traffic congestion in areas with two closely situated traffic lights is a complex issue that is often difficult to resolve. To address this issue, a coordination of timing between the two traffic controllers is proposed. This research conducts an experiment with two traffic controllers at two nearby intersections. The vehicle flow at each intersection is managed by the Agent acting as the traffic controller. The agent where more vehicles arrive is designated as the master agent, while the other agent is designated as the slave agent. A coordination algorithm is developed to synchronize the timing of the traffic controller so that the timing at the slave Agent was adjusted according to vehicle platoon arrivals from the master Agent. By this method, the green phase of the slave agent can be synchronized with the master agent, allowing vehicle platoons arriving from the master agent to immediately receive a green phase at the slave agent. This coordinated traffic control can be implemented with a microcontroller-based system, and vehicle movement can be simulated using Matlab's SimEvents. From the experiment conducted for two intersections located 500 meters apart, this scheme can reduce the average vehicle wait time from 40 seconds to just 9.4 seconds.